2024
DOI: 10.1002/adfm.202314031
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired, Bioactive, and Bactericidal: Anodized Nanotextured Dental Implants

Divya Chopra,
Tianqi Guo,
Anjana Jayasree
et al.

Abstract: Bioinspired titanium implant nanotexturing achieved via advanced techniques such as lithography, hydrothermal and laser patterning enables modulation of cell functions toward enhanced bioactivity and antibacterial efficacy. However, such costly, multi‐step methods limit clinical translation and benchtop implant modification. For the first time, single‐step, cost‐effective, and translatable electrochemical anodization is reported to fabricate bioinspired nanopillar‐like textures on micro‐rough titanium. In‐dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 140 publications
0
2
0
Order By: Relevance
“…120 In other words, the bacterial membrane cannot be easily stretched and spread on the surface with nanofeatures (eg, nanospears) causing perforation of the bacterial cell. 119,121 For example, Chopra et al have shown that nanopillar-like topographies including spinules, daggers, papillae, spikes, and flame could induce stretching in the bacterial membrane through adhesion forces which led to bacterial cell death. 121 In addition, the spinules and spikes with smaller sharp tips improved the antibacterial efficiency by the application of pressure on the membrane.…”
Section: Topography-mediated Antibacterial Performancementioning
confidence: 99%
See 1 more Smart Citation
“…120 In other words, the bacterial membrane cannot be easily stretched and spread on the surface with nanofeatures (eg, nanospears) causing perforation of the bacterial cell. 119,121 For example, Chopra et al have shown that nanopillar-like topographies including spinules, daggers, papillae, spikes, and flame could induce stretching in the bacterial membrane through adhesion forces which led to bacterial cell death. 121 In addition, the spinules and spikes with smaller sharp tips improved the antibacterial efficiency by the application of pressure on the membrane.…”
Section: Topography-mediated Antibacterial Performancementioning
confidence: 99%
“…119,121 For example, Chopra et al have shown that nanopillar-like topographies including spinules, daggers, papillae, spikes, and flame could induce stretching in the bacterial membrane through adhesion forces which led to bacterial cell death. 121 In addition, the spinules and spikes with smaller sharp tips improved the antibacterial efficiency by the application of pressure on the membrane. This finding indicated the key role of the sharpness of nanotopography in antibacterial properties.…”
Section: Topography-mediated Antibacterial Performancementioning
confidence: 99%